PHRASEOLOGICAL UNITS WITH THE PARTICIPATION OF “MOON” AND THEIR MEANINGFUL ANALYSIS (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article analyzes the semantic features of phraseological units in the Uzbek language containing the component “moon”. It examines their figurative meanings, degree of imagery, and stylistic functions in discourse. The study also identifies the place of the lexeme “moon” in the phraseological system and its role in creating expressiveness.